2015
DOI: 10.1186/s13002-015-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Farmers knowledge and perception on maize stem borers and their indigenous control methods in south western region of Cameroon

Abstract: BackgroundAgriculture is a major contributor to the Gross Domestic Product (GDP) of Cameroon, The South West region of Cameroon is known for its potential in the production of major agricultural commodities, but farmers’ yields from various speculations are low, dwindling over time due to some major constraints. Maize production is hampered by adverse socio-economic factors, several pests and diseases as well as high rainfall with low solar radiation. Lepidopterous maize stem borers are a major threat to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In the study area, only approximately 20% of farmers applied chemicals for stemborer control, whereas 80% used chemical-free cultural methods, including timely planting, the application of wood ash, the up-rooting of damaged maize stems and intercropping with other legume crops. Similarly, a study conducted by Oben et al [17] reported the use of different cultural methods, such as wood ash and botanicals, for the control of maize stem borers in Cameroon. In addition, Tefera [18] also indicated that intercropping and crop rotation of cereals with legumes decreased the incidence of pests, which resulted in increased yields.…”
Section: Discussionmentioning
confidence: 97%
“…In the study area, only approximately 20% of farmers applied chemicals for stemborer control, whereas 80% used chemical-free cultural methods, including timely planting, the application of wood ash, the up-rooting of damaged maize stems and intercropping with other legume crops. Similarly, a study conducted by Oben et al [17] reported the use of different cultural methods, such as wood ash and botanicals, for the control of maize stem borers in Cameroon. In addition, Tefera [18] also indicated that intercropping and crop rotation of cereals with legumes decreased the incidence of pests, which resulted in increased yields.…”
Section: Discussionmentioning
confidence: 97%
“…In sub‐Saharan Africa, the stemborers Busseola fusca (Fuller), Sesamia calamistis (Hampson) (both Lepidoptera: Noctuidae), and Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) are the economically most important lepidopteran pest species, severely limiting the yield of maize as they continuously infest the crop throughout its growth stages (Kfir et al, 2002; Oben et al, 2015). They may occur as single species or as a community of mixed species (Van Den Berg et al, 1991; Tefera, 2004; Ong’amo et al, 2006; Krüger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nyeko and Alubayo (2005) reported on termite management in Uganda, Tefera (2004) on sorghum stem borer management in Ethiopia, Oben et al (2015) on maize stem borers management in Cameroon, Gadisa and Birhane (2015) on Rodents control in Ethiopia, and Materu et al (2016) reported on management of tomato leaf miner in Tanzania.…”
Section: Introductionmentioning
confidence: 99%